SPOKEN THEATRE ACEH OF PMTOH PEUGAH HABA DEVELOPED BY TEUNGKU H. ADNAN: SPECTACLES STUDY - Afifuddin, Afifuddin; Sarwanto, Sarwanto; Murtana, I Nyoman (Srawung: Journal of Social Sciences and Humanities, 2023)
Peugah Haba is an oral literary art from Manggeng, Aceh. The tradition was adapted to a performance art by Mak Lapee in 1950 and then developed and popularised by Teungku H. Adnan since 1964. He called his theatre as PMTOH, the idea came from when he often rode the PMTOH bus when selling medicine, he was impressed by the sound of its horn and then practised it in every performance during Peugah Haba in Aceh. The theatre presented by Teungku Adnan is probably spectacles in a general, objective perspective. Therefore, this research is conducted to analyse the existence of props, costumes, and acting as part of the spectacle of peugah haba performed by Teungku Adnan PMTOH. The methodology used in this research is descriptive qualitative method. Meanwhile, in obtaining the data the researcher used documentary technique. The result of this research indicated that this spectacle addition brings novelty to the narration of the epic of Teungku Adnan theatre, especially in Acehnese hikayat. In addition, the existence of properties, costumes and additional acting in the spoken theatre facilitates the Acehnese people in interpreting the story.